Rancangan End-effector untuk Robot Pemanen Buah Paprika - I Dewa Made Subrata; Ichsan Nurfitra (Jurnal Keteknikan Pertanian, 2011)
Abstract A research on designing an end-effector for a sweet pepper (Capsicum grossum) harvesting robot has been conducted. The objectives of this research were to design an end-effector prototype for the sweet pepper harvesting robot and to examine the performance of the end-effector in actuating the harvesting work. The end-effector was constructed in such a way so that enable to perform cutting and gripping motion in one action. The end-effector was designed using aluminum materials in order to get as light mass as possible. It dimension was 28 cm in length, 14 cm in width, and about 90 grams in weight. The field test of the prototype was conducted based on the conditions of plantation inside the greenhouse. Three kinds of inclination  slope including 0o, 10o, and 20o were treated for the end-effector installation. The experimental result show that the third installation treatment ie: the end-effector with 20° inclination slope tend to produce the best performance which has the highest number of harvesting succeed. Keywords: end-effector, harvesting, sweet pepper. Abstrak Penelitian mengenai rancang bangun end-effector robot pemanen buah paprika (Capsicum grossum) telah berhasil dilakukan. Tujuan dari penelitian ini adalah merancang bangun prototype end-effector untuk memanen buah paprika dan menguji unjuk kerja dari end-effector tersebut dalam melakukan pekerjaan pemanenan. End-effector tersebut dibuat sedemikian rupa sehingga mampu melakukan gerak pemotongan dan pencengkraman dalam waktu bersamaan. End-effector dibuat menggunakan bahan aluminium supaya masanya menjadi ringan. End-effector mamiliki ukuran  panjang 28 cm, lebar 14 cm dan berat 90 gram. Pengujian terhadap prototype dilakukan sesuai kondisi tanaman dalam greenhouse. Tiga perlakuan nilai sudut kemiringan pemasangan yaitu: 0°, 10°, dan 20° dicobakan dalam pengujian ini. Hasil pengujian menunjukkan bahwa perlakuan ketiga yaitu end-effector dipasang dengan  kemiringan 20° cenderung memberikan unjuk kerja terbaik karena memberikan keberhasilan pemanenan tertinggi. Kata kunci: End-effector, pemanenan, buah paprika.Diterima: 15 Maret 2011 ; Disetujui: 18 Juli 2011